2008
DOI: 10.1007/s10461-008-9402-4
|View full text |Cite
|
Sign up to set email alerts
|

Latinos and HIV/AIDS: Examining Factors Related to Disparity and Identifying Opportunities for Psychosocial Intervention Research

Abstract: Latinos maintain an AIDS case rate more than 3 times higher than whites, a greater rate of progression to AIDS, and a higher rate of HIV/AIDS-related deaths. Three broad areas are reviewed related to these disparities: (1) relevant demographic, socioeconomic, and socio-cultural factors among Latinos; (2) drug abuse and mental health problems in Latinos relevant to HIV/AIDS outcomes; and (3) opportunities for psychosocial intervention. Latinos living with HIV are a rapidly growing group, are more severely impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 122 publications
0
60
0
Order By: Relevance
“…43,44 As of 2010, the U.S. Congress has been committed to eliminating inequalities in health through the creation of the National Center on Minority Health and Health Disparities. The research agenda of the NCMHD is geared toward addressing and improving healthcare outcomes and eliminating health disparities in the U.S. 43 Similarly in Texas, the Task Force on Health Disparities was established by Texas legislature in…”
Section: S) It Has Been Established That Americanmentioning
confidence: 99%
See 3 more Smart Citations
“…43,44 As of 2010, the U.S. Congress has been committed to eliminating inequalities in health through the creation of the National Center on Minority Health and Health Disparities. The research agenda of the NCMHD is geared toward addressing and improving healthcare outcomes and eliminating health disparities in the U.S. 43 Similarly in Texas, the Task Force on Health Disparities was established by Texas legislature in…”
Section: S) It Has Been Established That Americanmentioning
confidence: 99%
“…Kindness, or simpatía, is a welldocumented cultural normative value of Spanish-speaking patients. 13,41,42 Gonzalez et al 43 found that kindness was an especially important factor in the HIV patient-provider relationship. To our knowledge, no satisfaction studies with Spanish-speaking patients utilized an item that measured kindness (simpatía); however, Sleath et al 22 measured the importance of pharmacy employees being "nice," where 59.1 percent of Latino patients rated this quality was "very important."…”
Section: Satisfaction With the Demonstration Of Cultural Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 This bias may be somewhat balanced by the likelihood that IAIDS data overrepresents Hispanics, as a result of their greater likelihood to progress to AIDS, once HIV-infected 40 ; however, there are few data available to test this. CTS data represent only a small proportion of all HIV tests done in the USA and can include results for individuals tested more than once.…”
Section: Limitationsmentioning
confidence: 99%